Implementation of Hadith Learning in Fostering the Diversity of Students at SMP IT Raudhatul Ulum Sakatiga Palembang - Triansyah, Arief Agus; Annaqsyabandy, Bahaudin; Gunawan, Wawan; Alkayisy, Muhammad Ilyas (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The goal to be achieved from the implementation of Hadith lessons at SMP IT Raudhatul Ulum is to foster the diversity of students, to make students who live in an orderly and obedient manner adhere to the Islamic religion and students who are obedient in worship aretiqomah. The hope of this Hadith lesson is to make students who are